Development of Digital Teaching Materials for Short Story Texts with Critical Thinking Character for Junior High School Students - Supiah Supiah; Yusida Gloriani; Dede Endang Mascita (Universitas Pendidikan Mandalika, 2024)
This research aims to develop digital teaching materials for short story texts containing critical-thinking characters for junior high school students. This study used the research and development method with the ADDIE model, which includes five research stages: design, development, implementation, and evaluation. The data used were the results of expert validation of teaching materials and the results of implementation of the use of teaching materials for students. The data collection technique used a questionnaire, which was then analyzed descriptively and qualitatively. As a result of the analysis of short story text materials based on structure and content containing critical character content, five short stories were selected, namely Jono dan Kepala Sekolah, Di Penghujung Minggu, Radio 109.1 FM, Permainan Takdir, and Kode Ujian. Based on the validation results, the structure of the teaching materials consists of Title, Foreword, Learning Instructions, and Learning Introduction; Learning activity 1 contains listening elements, learning activity 2 contains reading and viewing elements, learning activity 3 contains speaking and presenting elements, learning activity 4 contains writing elements. Summary, evaluation, reflection, glossary and bibliography. The results of the implementation of teaching materials in two schools, each school using three classes, were obtained: an average score of 81.2, which can be concluded that the digital teaching materials of short story texts containing critical thinking which were implemented for class IX students can be said to be very suitable for use in Indonesian language learning.